Treatment of metastatic pancreatic neuroendocrine tumors: relevance of ENETS 2016 guidelines. Issue 2 (February 2017) - Foulfoin, Margaux; Graillot, Emmanuelle; Adham, Mustapha; Rousset, Pascal; Forestier, Julien; Hervieu, Valérie; Robinson, Philip; Scoazec, Jean-Yves; Lombard-Bohas, Catherine; Walter, Thomas
Abstract : The choice of first-line treatment for metastatic pancreatic neuroendocrine tumors (mP-NET) is mainly based on prognostic factors. ENETS-2016 guidelines stratified treatment according to 3 groups: Group 1, patients in whom all lesions could be removed; Group 2, patients with Ki67 <10%, low tumor burden, no symptoms and stable disease, for whom a watch-and-wait strategy or somatostatin analogs are proposed; Group 3, symptomatic patients or with Ki67 >10% or significant tumor burden or progressive disease, for whom a systemic chemotherapy is proposed. This retrospective study aimed to determine patient distribution, characteristics and outcome among these 3 groups. Patients with mP-NET diagnosis from 2004 to 2016 were categorized into the three groups. Prognosis was calculated using the Kaplan–Meier method. All treatments were recorded, and consistency with ENETS guidelines was explored. 104 patients were analyzed: 64% synchronous mP-NET, 80% grade 2 tumors and median overall survival (OS) of 104 (95% CI: 65–143) months. There were 15 patients in ENETS Group 1, 16 in Group 2 and 73 in Group 3. Median OS was not reached in Groups 1 and 2 and was 64 months (35–93) in Group 3. High liver tumor volume, high-grade tumor and progressive disease were associated with worse OS in multivariate analysis. The first-line treatment was in accordance with guidelines in 82%. 77% percent of deceased patients received less than 4 lines of treatment. Most patients are in Group 3 and do not receive all available treatments. Thus, trials are warranted to improve first-line chemotherapy. Alternative treatments may be considered for less aggressive disease.